Managing Organizational Capital in the Digital Age: A Study of Technology Adoption as a Competitive Advantage in Private Higher Institutions in South Sumatera - Irayani, Irayani; Kurnia Nengsih, Mimi; Herfianti, Meiffa (The Es Economics and Entrepreneurship, 2024)
This study investigates the management of organizational capital within the context of private higher institutions in South Sumatera, focusing on the adoption of technology as a means to gain a competitive advantage in the digital age. In today's rapidly evolving technological landscape, organizations are compelled to adopt digital innovations to enhance their operational efficiency, educational delivery, and overall performance. Using a qualitative research approach, this study explores the strategies and challenges faced by private higher institutions in South Sumatera as they navigate the complexities of technology adoption. The findings shed light on the various factors influencing the adoption of technology, including organizational culture, leadership support, resource availability, and external pressures. Moreover, the study examines how effective technology adoption contributes to organizational capital enhancement, enabling institutions to differentiate themselves and maintain competitiveness in the dynamic higher education sector. The insights derived from this research provide valuable implications for private higher institutions in South Sumatera and beyond, offering guidance on optimizing technology adoption strategies to harness the full potential of digital tools as a competitive advantage in the contemporary educational landscape.